Co-existence of multisystem inflammatory syndrome in children associated with COVID-19 and scrub typhus infection: a case series - Roy, Sarbani M.; Sahoo, Sushama (International Journal of Contemporary Pediatrics, 2021)
We are in the midst of pandemic of corona virus disease (COVID-19), caused by the novel coronavirus severe acute respiratory syndrome corona virus-2 (SARS-CoV-2). A clinical entity with hyperinflammatory syndrome, defined by World Health Organization (WHO) as multisystem inflammatory syndrome in children (MIS-C) and adolescents, temporarily related to COVID-19, is being reported in this pandemic from several countries. MIS-C has overlapping clinical features of Kawasaki disease (KD). KD has been described in association with various organisms including dengue, scrub typhus. MIS-C with concomitant infection has rarely been reported in literature till date. We report on ten sick pediatric patients presented with clinical features of MIS-C, in whom diagnosis of concomitant scrub typhus were also made. This retrospective study was conducted in the department of pediatric medicine of a medical college, in a district town of West Bengal, India. SARS-CoV-2 immunoglobulin G level was elevated in all of them and they were also positive with Scrub typhus serology. We reviewed and analysed their basic informations, clinical manifestations, epidemiological history, laboratory findings, treatment and short term outcome. Median age was 24 months (range 4 months-8 years), male: female was 1:1. All the patients survived. Concomitant tropical infection in a patient with MIS-C may play an important role in determining the prognosis of such patients. Early detection and intervention will result in better management and intact survival of them.